PERSEPSI MAHASISWA PROGRAM PENDIDIKAN GURU PROFESIONAL (PPG) PENDIDIKAN PENJASKESREK TERHADAP PROGRAM PPG - Siagian, Fera Ratna Dewi; Maria Andriani Barek Ladjar (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the perceptions of students in the Professional Teacher Education Program (PPG) for Physical Education, Health, and Recreation (Penjaskesrek) regarding the implementation of the PPG program based on several indicators: program objectives, materials and curriculum, learning process, lecturer competency, facilities and infrastructure, and program outcomes. This study used a descriptive quantitative approach with a survey method. The sample size was 23 PPG Penjaskesrek students. The instrument used was a questionnaire with a rating scale based on the six indicators. Data were analyzed using descriptive statistics in percentages.The results showed that, in general, students' perceptions of the PPG program were in the good category. The program objectives were deemed clear and aligned with the needs of prospective teachers, the materials and curriculum were deemed relevant to the demands of school learning, and the learning process was deemed quite effective in supporting student understanding. Lecturers' competency in delivering material and guiding students was also perceived as good. Facilities and infrastructure were deemed adequate, although some limitations remained. Meanwhile, program outcomes indicated an increase in students' professional competency as prospective Penjaskesrek teachers. Thus, the quality of the PPG program needs to be continuously improved to be more optimal in producing professional and competent teachers.